Reproducible Research is like riding a bike - Granell, C. (2020)
Reproducibility is a fundamental pillar in science but it has recently been described as hard and challenging to achieve, as stated in numerous editorials and papers, some of which alert on a “reproducibility crisis”. In this article we outline 1/ the approach taken to put Reproducible Research (RR) in the agenda of the GIScience community, 2/ first actions and initial lessons learned towards the discussion and adoption of RR principles and practices in the workflows and habits of researchers, and finally, we present 3/ our short-term strategy (two years) and specific actions to achieve the main goal of making RR an integral part of scientific workflows of the GIScience community.